Winter Wheat Vernalization Alleles and Freezing Tolerance at the Seedling and Jointing Stages - Fangfang Liu; Wenxin Cao; Qiqi Zhang; Yao Li; Heng Zhou; Yingxiu Wan (Plants)
This study explores the relationship between allelic variation of the vernalization genes (VRN) and the freezing tolerance at the seedling and jointing stages of winter wheat growth. It provides a basis for molecular marker development for freezing tolerance breeding of winter wheat. A total of 435 wheat accessions were used to identify and evaluate the freezing tolerance at the seedling stage using field tests, while 192 wheat accessions were used to evaluate the freezing tolerance at the jointing stage in climate chamber tests. The VRN genes of the wheat accessions were detected using allele-specific markers of the VRN-A1, VRN-B1, VRN-D1 and VRN-B3 loci, and the relationship between VRN genotype and freezing tolerance at the two developmental stages was tested. There were significant differences in freezing tolerance between the wheat accessions. Assessing the freezing tolerance of 52 wheat accessions at both the seedling and jointing stages revealed no significant correlation between tolerance at these two stages. The genotypic analysis found that Vrn-D1 was the most frequent dominant allele in winter wheat, while no accession contained the dominant alleles Vrn-A1 and Vrn-B3. Notably, freezing tolerance showed stage-specific genetic regulation; seedling-stage freezing tolerance strongly correlated with vernalization gene allelic combinations (p < 0.05), whereas jointing-stage freezing tolerance exhibited no such association. The presence of all recessive alleles vrn-A1, vrn-B1, vrn-D1 and vrn-B3 was required for strong seedling-stage freezing tolerance. The VRN-D1 marker was effective for screening freezing tolerance materials under the premise that vrn-A1 and vrn-B1 alleles are recessive at winter wheat seedling stage.